The name jar - Choi, Yangsook (New York : Alfred A. Knopf, 2001)
After Unhei moves from Korea to the United States, her new classmates help her decide what her name should be.
Book Links (A.L.A.).
Booklist.
New York Times.
4.1
K-3
Center for the Collaborative Classroom Curriculum.
Keywords: Names, Personal -- Fiction; Identity -- Fiction; Korean Americans -- Fiction; Schools -- Fiction; Personal names -- Fiction; School stories